Dissipative control of uncertain dynamical systems - Xie, Shoulie. (2009)
This thesis reports the research work on dissipative control for dynamical systems with or without uncertainties. In particular, we focus on quadratic dissipativity. First, we consider the dissipative analysis for linear systems and establish necessary and sufficient conditions for quadratic dissipativity in terms of algebraic Riccati equations (AREs) or linear matrix inequalities (LMIs). We then apply the analysis results to dissipative control problem for linear systems via state feedback and linear dynamical output feedback control.